Subclinical atherosclerosis in patients with rheumatoid arthritis - Ambrosino, Pasquale; Lupoli, Roberta; Di Minno, Alessandro; Tasso, Marco; Peluso, Rosario; Di Minno, Matteo Nicola Dario (Thrombosis and Haemostasis, 2015)
We performed a systematic review with meta-analysis and meta-regression of literature studies evaluating the impact of rheumatoid arthritis (RA) on common carotid artery intima-media thickness (CCAIMT) and on the prevalence of carotid plaques. Studies evaluating the relationship between RA and markers of cardiovascular (CV) risk (CCA-IMT and prevalence of carotid plaques) were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases. A total of 59 studies (4,317 RA patients and 3,606 controls) were included in the final analysis, 51 studies with data on CCA-IMT (52 data-sets on 3,600 RA patients and 3,020 controls) and 35 studies reporting on the prevalence of carotid plaques (2,859 RA patients and 2,303 controls). As compared to controls, RA patients showed a higher CCA-IMT (mean difference [MD]: 0.10 mm; 95 % confidence interval [CI]: 0.07, 0.12; p < 0.00001), and an increased prevalence of carotid plaques (odds ratio [OR]: 3.61; 95 %CI: 2.65, 4.93; p< 0.00001). Interestingly, when analysing studies on early RA, the difference in CCAIMT among RA patients and controls was even higher (MD: 0.21 mm; 95 %CI: 0.06, 0.35; p=0.006), and difference in the prevalence of carotid plaques was entirely confirmed (OR: 3.57; 95 %CI: 1.69, 7.51; p=0.0008). Meta-regression models showed that male gender and a more severe inflammatory status [as expressed by disease activity score in 28 joints (DAS28), C-reactive protein (CRP) levels, and erythrocyte sedimentation rate (ESR)] significantly impacted on CCA-IMT. In conclusion, RA appears significantly associated with subclinical atherosclerosis and CV risk. These findings can be useful to plan adequate prevention strategies and therapeutic approaches.
Keywords: Rheumatoid arthritis; cardiovascular risk; intima-media thickness; carotid plaques